Evaluation of Ambient Air Quality in Faisalabad, Pakistan - Iqbal, M.; Niaz, Y.; Mushtaq, M.; Khera, R.A.; Cecil, F.; Waqar, M.A.; Abbas, M.; Bokhari, T.H. (Asian Journal of Chemistry, 2012)
According to air quality standards of NEQS and USEPA, the air quality parameter such as oxides of nitrogen (NOx), sulphur (SOx) and carbon (CO) and their variation in Faisalabad, Pakistan has been evaluated. The concentrations of these pollutants were measured at 24 different sites for the period of three month. Results showed that concentration of NOx, SOx and CO were higher in the ambient air of Faisalabad city during the month of June and July and NOx reduced lower the limits of NEQS in August, but still higher than the USEPA ambient air quality standards while the level SOx and CO was found higher than both the NEQS and USEPA standards throughout the study period. The variation in NOx and SOx level was also found significant (p < 0.05) in different periods and station. Furthermore, it is found that the vehicular and industrial areas were the major contributor as compared with residential/commercial areas.